Back to the future revisited: A systematic literature review of performance-related pay in the public sector - Ahmad, Farooq; Lyu, Jing (Daisy); Stazyk, Edmund; Higgs, Malcolm (International public management journal, 2024)
Performance-related pay (PRP) has been part of public-sector pay structures in the past four decades. Despite public administration scholars denouncing its use in the public sector, PRP is being increasingly implemented in public organizations worldwide. Notwithstanding controversy over its use in the public sector, the last decade has seen a huge surge in its adoption. In order to assess the theoretical, empirical, and scientific reasoning for this interest we analyze the existing literature in order to identify the emerging discussions in this area and to provide a systematic review that can be used as guidance for future research. The review highlights the gaps in our current knowledge of PRP in the public sector and identifies factors affecting its success that have emerged from new research over the last fourteen years. After identifying these, we propose a number of important pathways that future research might take in order for public organizations globally to design optimal PRP schemes.